Designing Units with the Ubd Framework to Teach English as a Foreign Language: Benefits and Challenges - Evrim Eveyik Aydın; Gülşah Çelikman Hanratty (Sakarya University Journal of Education)
This study aims to explore English language teachers’ and English department heads’ perspectives on the benefits and challenges of designing and delivering units using Understanding by Design (UbD) framework to teach English as a Foreign Language (EFL). UbD is a unit and curriculum design framework which aims for student understanding and its transfer into real life context through three stages: identifying the desired results, determining the assessment evidence, and planning learning activities. Data was collected through open-ended questionnaires from 39 English language teachers and five department heads, and semi-structured focus group interviews with seven teachers. The content and thematic analysis of the qualitative data revealed that the teachers who implemented UbD within the context of their school perceived it as a design process with benefits on students’ academic achievement and English language skills through its focus on the development of understandings and transfer. The findings also uncovered perceived challenges caused by institutional, instructional, teacher related and learner related factors. Teachers also found UbD implementations challenging due to the characteristics of online education during the global pandemic. These findings suggest that although UbD is not commonly used at schools in the Turkish EFL context, it can be offered as an alternative unit design practice if teachers’ professional knowledge of its underlying principles is increased with regular in-service trainings on its proper implementation.